Rohdea dangii (Asparagaceae), a new species from northwestern Vietnam - Nguyen, Khang Sinh; Tanaka, Noriyuki; Averyanov, Leonid V.; Nguyen, Phuong Hanh; Tran, Duc Binh (Phytotaxa, 2021)
Rohdea dangii, a new species from limestone areas of Son La and Dien Bien Provinces in northwestern Vietnam, is described and illustrated. It is apparently most closely related to R. tonkinensis described from northern Vietnam, for these two species share an elongate aerial stem with no cataphylls (except for those at the base of the peduncle), narrowly elliptic leaf blades and filaments conspicuously incrassate in the lower decurrent portions. It is, however, readily distinguishable mainly by the longer, thicker rhizome, non-sheathing amplexicaule leaf blades, half-terete peduncle, much shorter bracts mostly not exceeding the flowers, and crateriform perigone tube. The taxonomic relationships of the new species to R. wattii and two other species with an aerial stem were also briefly discussed.